1973
DOI: 10.1111/j.1365-2621.1973.tb01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Discolouration in pre‐packaged beef: measurement by reflectance spectrophotometry and shopper discrimination

Abstract: When bright red beef and discoloured beef are sold together, shropper discrimination against the discoloured meat increases with increase in metmyoglobin content. The relationship between the level of discolouration in terms of metmyoglobin content and the proportion of total sales of discoloured meat is linear over the range tested, 5-33% metmyoglobin. 'The ratio of sales of discoloured beef to bright red beef is approximately 1 : 2 when 20%, metmyoglobin is present in the discoloured batch. There is clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(40 citation statements)
references
References 6 publications
0
37
0
2
Order By: Relevance
“…7 n-3, sum of 20 : 4n-3, 20 : 5n-3, 22 : 5n-3, 22 : 6n-3. Chicory and beef quality rejection during the purchase of fresh beef (Hood and Riordan, 1973). Beef colour stability is known to differ among muscle type, with the M. Longissimus muscle being the most stable (O'Keeffe and Hood, 1982) and, therefore the findings reported here are only in reference to this muscle and may have differed if other muscle types were studied.…”
mentioning
confidence: 44%
“…7 n-3, sum of 20 : 4n-3, 20 : 5n-3, 22 : 5n-3, 22 : 6n-3. Chicory and beef quality rejection during the purchase of fresh beef (Hood and Riordan, 1973). Beef colour stability is known to differ among muscle type, with the M. Longissimus muscle being the most stable (O'Keeffe and Hood, 1982) and, therefore the findings reported here are only in reference to this muscle and may have differed if other muscle types were studied.…”
mentioning
confidence: 44%
“…Parameters related with OMb have less pronounced evolution, A O and KS O decrease with time but differences become significant only between days 4 and 7. During the studied period the proportion of MMb was assumed to increase, but it was always less than the proportion of OMb (Hood and Riordan 1973;Renerre and Mazuel 1985). The slow decrease in the A O and KS O , correlated with OMb content, the pigment that gave vivid red color to meat, agreed with the slow decay of a* and C*.…”
Section: Resultsmentioning
confidence: 99%
“…As the proportion of metmyoglobin increases meat color turns to brown. This induces a negative response in consumers and when the proportion of MMb reaches 20% it has been found that the product is rejected by half of the potential consumers (Hood and Riordan 1973;Renerre and Mazuel 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These values are close to the 20 % of MMb that has been used as a cut off for consumer rejection (Hood and Riordan 1973;Renerre and Mazuel 1985). However we cannot be sure that this concordance is casual or it can be considered an expected behavior in any situation.…”
Section: Resultsmentioning
confidence: 99%
“…Color deterioration in meat surface is due to the appearance of metmyoglobin, the myoglobin oxidized state. As the proportion of metmyoglobin increases meat color turns to brown, this induces a negative response in consumers and when the proportion of MMb reaches 20 % it has been found that the product is rejected by half of the potential consumers (Hood and Riordan 1973;Renerre and Mazuel 1985).…”
Section: Introductionmentioning
confidence: 99%